2023
DOI: 10.3390/ijms24065078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l-Arginine Plus Vitamin C Supplementation on l-Arginine Metabolism in Adults with Long COVID: Secondary Analysis of a Randomized Clinical Trial

Abstract: Altered l-arginine metabolism has been described in patients with COVID-19 and has been associated with immune and vascular dysfunction. In the present investigation, we determined the serum concentrations of l-arginine, citrulline, ornithine, monomethyl-l-arginine (MMA), and symmetric and asymmetric dimethylarginine (SDMA, ADMA) in adults with long COVID at baseline and after 28-days of l-arginine plus vitamin C or placebo supplementation enrolled in a randomized clinical trial, compared with a group of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…However, the persistent hyper-inflammatory state and immune dysregulation which is common among virus-free PASC patients, arginine supplementation may prove beneficial to this group. In PASC pathology, the markers of NO• bioavailability are low; accordingly, oral supplementation of these patients with l -arginine + vitamin-C for 4 weeks could significantly elevate serum l -arginine levels and thereby increase NO• bioavailability 419 . In another human RCT ( n = 50), oral supplementation of l -arginine (1.66 g/d) + vit-C (500 mg/d) for 4 weeks restored physical performance, endothelial function, fatigue, and relieved persistent symptoms in PASC patients 415 .…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…However, the persistent hyper-inflammatory state and immune dysregulation which is common among virus-free PASC patients, arginine supplementation may prove beneficial to this group. In PASC pathology, the markers of NO• bioavailability are low; accordingly, oral supplementation of these patients with l -arginine + vitamin-C for 4 weeks could significantly elevate serum l -arginine levels and thereby increase NO• bioavailability 419 . In another human RCT ( n = 50), oral supplementation of l -arginine (1.66 g/d) + vit-C (500 mg/d) for 4 weeks restored physical performance, endothelial function, fatigue, and relieved persistent symptoms in PASC patients 415 .…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…After 28 days of l-arginine plus vitamin C supplementation, serum l-arginine concentrations increased significantly compared with placebo. This supplement may therefore be proposed as a remedy to increase NO bioavailability in people with long COVID-19 [119].…”
Section: L-arginine With Vitamin Cmentioning
confidence: 99%
“…Some studies reported the beneficial effects of vitamin C and L-arginine on walking capacity, muscle strength, endothelial function and fatigue in adults with Long COVID [155,156]. Considering their effects on aerobic and anaerobic performance in patients with cardiopulmonary diseases including HF or heart transplant, their potential efficiency in combination with a physical activity rehabilitation program may be one of the key medical strategies for Long COVID patients.…”
Section: Long Covid-potential Management Directionsmentioning
confidence: 99%